(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Participation of workers in management of state enterprises constitutes a problem of many aspects. We must be conscious of that while discussing its legal aspects and thus we should consider together political, sociological, economic, psychological, legal and prakseological aspects of this problem. From the very beginning of People’s Power participation of working masses in management of state affairs was considered one of the principles of building socialist society. Participation of wokers in management of a state enterprise is one of legal forms to realize this principle. To begin, the decree of 1945 on workplace councils was passed. Further legal regulation was brought by the law on workers’ councils of 1956 and later by the law on workers’ self government cooperation of 1958. And since 1970 article 13 of the Constitution of the Polish people’s Republic expresses the principle of participation of workers of state enterprises in management of state enterprises as one of the principles of political system. It will be further developed by other legal acts. Legal regulation serving the realization of the principle of participation of workers in management of state enterprises should provide for such solutions and legal instruments which would: guarantee that the employees presents its opinion in all matters concerning the enterprise; promote personal engagement of employees in the affairs of the enterprise and especially in matters of good (economic) management and execution of tasks; influence elimination of elements favouring existence of relicts of the division “we — the employees — and they — the managers of the enterprise”; introduce the employees and its authentic re- presentation as a partner to manage the enterprise. Finally, it should constitute an element influencing the consciousness, sense of duty and common responsibility for the affairs of a state enterprise.